2013
DOI: 10.4049/jimmunol.1300216
|View full text |Cite
|
Sign up to set email alerts
|

Active Caspase-3 Is Stored within Secretory Compartments of Viable Mast Cells

Abstract: Caspase-3 is a main executioner of apoptotic cell death. The general notion is that, in viable cells, caspase-3 is found as a cytosolic inactive proenzyme and that caspase-3 activation is largely confined to processes associated with cell death. In this study, we challenge this notion by showing that enzymatically active caspase-3 is stored in viable mast cells. The enzymatically active caspase-3 was undetectable in the cytosol of viable cells, but was recovered in subcellular fractions containing secretory gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
2
14
0
2
Order By: Relevance
“…3). In addition, we observed an increase in cleaved caspase‐3 in the form of granules—similar to those previously described in viable mast cells (46)—as a result of TDP43 treatment (Fig. 3).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…3). In addition, we observed an increase in cleaved caspase‐3 in the form of granules—similar to those previously described in viable mast cells (46)—as a result of TDP43 treatment (Fig. 3).…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, Hsp27 was found to dramatically suppress the number of caspase‐3 granules of TDP‐43–exposed cells and to slightly increase activated caspase‐3 total levels, which supports a role for caspase‐3 in IL‐18 alternative processing in microglia. Of interest, active caspase‐3 granule‐like compartments have been previously found in viable mast cells (46); therefore, the observed results with Hsp27 cotreatment may suggest an actual increase in caspase‐3 intracellular availability. If so, the incremented neurotoxic effects of TDP‐43–exposed microglia by Hsp27 cotreatment may be related to an exacerbated neuroinflammatory/neurotoxic profile that is linked to IL‐1β/‐18 and activated caspase‐3 (44, 67).…”
Section: Discussionmentioning
confidence: 64%
“…The presence of active caspase‐3 in MC granules was recently reported . We extend this observation by employing WT and gzmB‐deficient mice to show that cleavage of pro‐caspase‐3 and its granular storage is strictly regulated by gzmB.…”
Section: Discussionsupporting
confidence: 67%
“…1E), suggesting that the processed form of caspase-3 represents fully operative caspase-3. Not explainable at the moment is the observation that supernatants of unstimulated BMMCs also contain caspase-3-like activity, which was also reported by Garcia-Faroldi et al [6]. Previously, we reported that gzmB is stored in secretory lysosomes of mouse MCs, both in vivo and in vitro [7].…”
Section: Mouse Mcs Constitutively Express Cleaved Active Caspase-3 Anmentioning
confidence: 54%
“…After washing, cells were resuspended in DMEM media and aliquots of 100 μ L were dropped into round areas (prepared using liquid‐repellent slide marker pen) on microscopic glasses, followed by confocal microscopy analysis as described (Garcia‐Faroldi et al. ).…”
Section: Methodsmentioning
confidence: 99%